Association Between Prepregnancy Cardiovascular Function and Subsequent Preeclampsia or Fetal Growth Restriction. Issue 2 (August 2018) - Foo, Fung L.; Mahendru, Amita A.; Masini, Giulia; Fraser, Abigail; Cacciatore, Stefano; MacIntyre, David A.; McEniery, Carmel M.; Wilkinson, Ian B.; Bennett, Phillip R.; Lees, Christoph C.
Abstract : Preeclampsia and fetal growth restriction during pregnancy are associated with increased risk of maternal cardiovascular disease later in life. It is unclear whether this association is causal or driven by similar antecedent risk factors. Clarification requires recruitment before conception which is methodologically difficult with high attrition rates and loss of outcome numbers to nonconception/miscarriage. Few prospective studies have, therefore, been adequately powered to address these questions. We recruited 530 healthy women (mean age: 35.0 years) intending to conceive and assessed cardiac output, cardiac index, stroke volume, total peripheral resistance, mean arterial pressure, and heart rate before pregnancy. Participants were followed to completion of subsequent pregnancy with repeat longitudinal assessments. Of 356 spontaneously conceived pregnancies, 15 (4.2%) were affected by preeclampsia and fetal growth restriction. Women who subsequently developed preeclampsia/fetal growth restriction had lower preconception cardiac output (4.9 versus 5.8 L/min; P =0.002) and cardiac index (2.9 versus 3.3 L/min per meter 2 ; P =0.031) while mean arterial pressure (87.1 versus 82.3 mm Hg; P =0.05) and total peripheral resistance (1396.4 versus 1156.1 dynes sec cm − 5 ; P <0.001) were higher. Longitudinal trajectories for cardiac output and total peripheral resistance were similar between affected and healthy pregnancies, but the former group showed a more exaggerated fall in mean arterial pressure in the first trimester, followed by a steeper rise and a steeper fall to postpartum values. Significant relationships were observed between cardiac output, total peripheral resistance, and mean arterial pressure and gestational epoch. We conclude that in healthy women, an altered prepregnancy hemodynamic phenotype is associated with the subsequent development of preeclampsia/fetal growth restriction. Abstract : Supplemental Digital Content is available in the text.